2008
DOI: 10.1080/09593980701704089
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of posture and psychosocial factors as contributors to upper quadrant musculoskeletal pain in children and adolescents

Abstract: Musculoskeletal pain has become a major symptomatic complaint among children and adolescents and is increasingly occurring at a younger age. This systematic review was done to evaluate the evidence for the contribution of posture and psychosocial factors to the development of upper quadrant musculoskeletal pain in children and adolescents. The review describes the measurement tools used to assess musculoskeletal pain, sitting posture, and psychosocial factors. Two independent reviewers searched seven databases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
2
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 38 publications
3
46
2
2
Order By: Relevance
“…16 Recent reviews, both in adult and in child populations, show that sleep problems are common in those with pain 16,17 and that in adults sleep problems are more likely to precede pain (risk of new episodes of pain) in contrast to pain as a predictor of sleep problems. 16 Previous systematic reviews [18][19][20][21][22][23] on risk factors for musculoskeletal pain onset in children and adolescents have been carried out but have not yet considered the potential role of sleep problems as a risk factor for musculoskeletal pain onset in these populations. The aim of this systematic review is to evaluate evidence from prospective studies that investigated if children and adolescents with sleep problems are at higher risk for the onset of musculoskeletal pain.…”
Section: Introductionmentioning
confidence: 99%
“…16 Recent reviews, both in adult and in child populations, show that sleep problems are common in those with pain 16,17 and that in adults sleep problems are more likely to precede pain (risk of new episodes of pain) in contrast to pain as a predictor of sleep problems. 16 Previous systematic reviews [18][19][20][21][22][23] on risk factors for musculoskeletal pain onset in children and adolescents have been carried out but have not yet considered the potential role of sleep problems as a risk factor for musculoskeletal pain onset in these populations. The aim of this systematic review is to evaluate evidence from prospective studies that investigated if children and adolescents with sleep problems are at higher risk for the onset of musculoskeletal pain.…”
Section: Introductionmentioning
confidence: 99%
“…Such an approach should incorporate factors from all domains of the biopsychosocial model, including developmental, educational and cultural background [14][15][16][17][18]. Earlier studies [9,13,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] and reviews [15,[35][36][37][38][39][40][41] identifying risk factors for IASP have attempted to evaluate the contribution of multiple different physical, psychosocial, demographic, environmental and socioeconomic factors to the development of spinal pain at young age, mostly in relation to low back pain (LBP) [9,19,20,[22][23][24][25][26][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…In a systematic review, Prins et al [48] concluded that LBP may be influenced by the sitting posture in children and adolescents and a correlation has been observed between spinal posture and LBP [45]. In particular, the risk of LBP increases in sedentary workers, with symptoms increasing during sitting for longperiods of time [47].…”
Section: Discussionmentioning
confidence: 99%